2005
DOI: 10.1177/0273475304273346
|View full text |Cite
|
Sign up to set email alerts
|

The Motivational Effects of the Classroom Environment in Facilitating Self-Regulated Learning

Abstract: Students can be proactive and engaged or, alternatively, lack initiative and responsibility for their learning. Self-regulated learning involves learning strategies and mental processes that learners deliberately engage to help themselves learn and perform better academically. The results of this study provide empirical support for the theoretical relationships among cognitive evaluation theory, achievement goal theory, and self-regulated learning strategies in the context of the classroom. Superficial learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
178
1
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(217 citation statements)
references
References 69 publications
12
178
1
12
Order By: Relevance
“…The technique has been worldwide used in teaching practice for many decades. Among its advantages RJW they mention development of motivation and clearly demonstrate the link between implementation of Reflective Journal (RJ) and motivation enhancement in learners (Farrah, 2012;Walker, 2006;Lear, 2013;Young, 2014).…”
Section: Research Questionsmentioning
confidence: 99%
“…The technique has been worldwide used in teaching practice for many decades. Among its advantages RJW they mention development of motivation and clearly demonstrate the link between implementation of Reflective Journal (RJ) and motivation enhancement in learners (Farrah, 2012;Walker, 2006;Lear, 2013;Young, 2014).…”
Section: Research Questionsmentioning
confidence: 99%
“…The presence of a number of educational mission declarations asserting their attempts and attainments in improving this characteristic in learners also requires the supposition of autonomy for learners. In an educational setting, there are different terms used for the concept of autonomy such as self-managed learning (Greenberg, 1987;Risemberg & Zimmerman, 1992;Wolters, 1998), self-directed learning (Biemiller & Meichenbaum, 1992), self-controlled learning (Anderson & Prawat, 1983;Zimmerman & Martinez-Pons, 1990), self-initiated learning (Lindner & Harris, 1993;Purdie & Hattie, 1996), self-motivated learning (Alderman, 1999;Ames, 1992;Stipeck, 1993;Young, 2005). Regardless of these various phrases used for the issue of autonomy, only self-regulated learning has gained significance in representing the issue of autonomy in its academic meaning (Boekarts, 2002;Corno, 2001;Zimmerman, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The three theories emphasize the importance of appropriately challenging academic work for students and stressed the importance of a sense of ownership over the learning process (Urdan & Schoefelder, 2006). Meanwhile, Young (2005) states that the cognitive evaluation theory also explains effect of learning environment on learning motivation. Cognitive evaluation theory tests the perceived competency (self-efficacy) and task value affects the motivation.…”
Section: Motivation In Learningmentioning
confidence: 99%
“…According to Young (2005), learning environment can affect self-regulated learning and learning motivation. Results of previous studies have consistently shown that the learning environment affect students' academic self-efficacy and students' self-efficacy beliefs in academic performance and affect the improvement of learning environment and students' achievement (Velayutham & Aldrige, 2013).…”
Section: Introductionmentioning
confidence: 99%